2019
DOI: 10.3389/fpls.2019.00208
|View full text |Cite
|
Sign up to set email alerts
|

Flavanone-3-Hydroxylase Plays an Important Role in the Biosynthesis of Spruce Phenolic Defenses Against Bark Beetles and Their Fungal Associates

Abstract: Conifer forests worldwide are becoming increasingly vulnerable to attacks by bark beetles and their fungal associates due to the effects of global warming. Attack by the bark beetle Ips typographus and the blue-stain fungus it vectors ( Endoconidiophora polonica ) on Norway spruce ( Picea abies ) is well known to induce increased production of terpene oleoresin and polyphenolic compounds. However, it is not clear whether specific compounds ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 80 publications
(140 reference statements)
4
49
0
1
Order By: Relevance
“…[31,34]. Additionally, in vitro studies indicate that stilbene glucosides inhibit the fungal growth of E. polonica [52,55,56]. This supports the idea that (+)-catechin has an important role in conifer defense against fungal pathogens.…”
Section: Induced Tissue and Cell-level Responses To Wounding And Fungsupporting
confidence: 61%
“…[31,34]. Additionally, in vitro studies indicate that stilbene glucosides inhibit the fungal growth of E. polonica [52,55,56]. This supports the idea that (+)-catechin has an important role in conifer defense against fungal pathogens.…”
Section: Induced Tissue and Cell-level Responses To Wounding And Fungsupporting
confidence: 61%
“…Molecular-genetic methods for up-or downregulation of gene expression in plants provide numerous opportunities for exp er i m en t al m an i p u l a t i on of p l a n t bi o ch e m i s t r y (Hammerbacher et al 2019;Tian et al 2015), but also for investigating the effects of specific plant compounds on feeding behavior and performance of associated herbivores (Kosonen et al 2012;Müller et al 2015;Sasse et al 2016). In our study, inhibition of DFR and ANR activity altered the chemo-and phenotype of young B. pendula.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, leaf infection by the rust fungus, M. larici-populina , also resulted in the accumulation of flavan-3-ols which reached a maximum level during the sporulation phase of the fungus (Ullah et al, 2017). Other studies have also shown that catechin and PAs accumulate in tree stems upon pathogen infection as anti-microbial defenses (Barry et al, 2002; Danielsson et al, 2011; Hammerbacher et al, 2019). In agreement, catechin and PAs accumulated densely around the point of inoculation in the bark and cambium tissues of P. populi -infected poplar stems compared to the adjacent stem internodes.…”
Section: Discussionmentioning
confidence: 96%